Autoimmune arthritis induces paired immunoglobulin‐like receptor B expression on CD4+ T cells from SKG mice. Issue 9 (27th July 2017) - Rothe, Kathrin; Raulien, Nora; Köhler, Gabriele; Pierer, Matthias; Quandt, Dagmar; Wagner, Ulf
Abstract : In chronic autoimmune SKG arthritis, a large fraction of CD4 + T cells upregulate expression of the inhibitory receptor PIR‐B and show increased secretion of IL‐17 and IFN‐γ, indicative of their involvement in the autoimmune disease. Unexpectedly, increased frequencies of IFN‐γ producing PIR‐B + CD4 + T cells appear to ameliorate the disease, suggesting that they have an inhibitory function. Abstract: The chronic, destructive autoimmune arthritis in SKG mice, which closely resembles human rheumatoid arthritis, is the result of self‐reactive T cells escaping thymic deletion. Since the inhibitory receptor LIR‐1 is up‐regulated on auto‐reactive T cells in human rheumatoid arthritis, the role of its murine ortholog PIR‐B was investigated. Peripheral CD4 + T cells from SKG mice were found to frequently express PIR‐B, and this population produces more frequently IL‐17 upon in vitro stimulation compared to PIR‐B − cells. A much larger fraction of PIR‐B + T cells, however, was found to secret no IL‐17, but IFN‐γ. With regards to the clinical course of the disease, high frequencies of PIR‐B + CD4 + T cells were found to be associated with a milder course of arthritis, suggesting that the net effect of PIR‐B expression is suppression of autoreactive T cells. Our results indicate that overexpression of PIR‐B on IL‐17‐producing SKG CD4 + T cells might represent an effective counter‐regulatory mechanism against the destructive potential of those cells. More importantly, a major population of PIR‐B + T cells in SKG mice appears to play an inhibitory role by way of their IFN‐γ production, since high frequencies of those cells ameliorate the disease.